Analisis Faktor Penentu Tingkat Service Per Conception Pada Sapi Bali Di Kawasan Peternakan Kabupaten Tebo - Fachroerrozi Hoesni; Firmansyah Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study was to analyze the achievement of service per conception (S/C) and the most dominant determinant of determining the level of S / C in Bali cattle in the cattle breeding area of Tebo Regency. The research method used was survey and laboratory, with cluster random sampling technique. The sample size in this study was determined using the iterative method. The analysis model used is path analysis.The results of the research on the Cattle Farming Area in Tebo Regency which includes Rimbo Bujang District, Rimbo Ulu District and Rimbo Ilir District obtained data, namely the success rate of artificial insemination (IB) in Bali cattle as reflected in the S / C is an average of 1.55 ± 0.36. This performance is quite good. Based on the standards set by the Directorate General of Animal Husbandry and Animal Health, the majority of S/C levels in Bali cattle in the Tebo Regency Cattle Farming Area have reached IB Swadaya services (65.43%). This study concluded that the adequacy of feed given to cattle is the most determining factor in the success of AI in Bali cattle in the cattle breeding area in Tebo Regency which is reflected in the S/C